FAKTOR YANG BERHUBUNGAN DENGAN KEIKUTSERTAAN KB PADA PASANGAN USIA SUBUR DI KELURAHAN WATANG SUPPA KECAMATAN SUPPA KABUPATEN PINRANG TAHUN 2 - Nurdin, Fitriani (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
The program has an important contribution to national KB in an effort toimprove the quality of HUMAN RESOURCES through education contributionprogram national KB. Renstra MPS (plan national strategies MakingPregnancy Safer) aims to decrease maternal mortality amounted to 75% by2015, from AKI in 1990 and neonatal mortality to less than 35 per 1000 livebirths by 2015. On the implementation of the program of Making PregnancySafer (MPS) in Indonesia 2002-2010 is that every pregnancy should be adesired pregnancy. To realize these key messages, KB is the efforts of preventivehealth services to the most basic and primary.This type of research is observational approach cross sectional study i.e. toknow factors related to participation in family planning couples of fertile age inKelurahan Watang Subdistrict Suppa Suppa Pinrang Regency 2014 areobserved in the same time period. This research was carried out in KelurahanWatang Subdistrict Suppa Suppa Pinrang Regency Year for 30 days starting onOctober 1 – April 30, 2014 by taking a sample of 50 pairs of fertile age.Results of the study found that the level of education associated with theparticipation of family planning in the fertile age couples in Kelurahan WatangSubdistrict Suppa Suppa Pinrang Regency 2014 as much 72.2% and the value ofp (0,017), revenue associated with the participation of family planning in thefertile age couples in Kelurahan Watang Subdistrict Suppa Suppa PinrangRegency 2014 as much 81.5% and the value of p (0.002), distance related to theparticipation of family planning in the fertile age couples in Kelurahan WatangSubdistrict Suppa Suppa Pinrang Regency 2014 as much 79.4% and the value ofp (0.000), support the husband related to participation in family planningcouples of fertile age associated with the participation of family planning in thefertile age couples in Kelurahan Watang Subdistrict Suppa Suppa PinrangRegency 2014 as much as 87% and the value of p (0.001). For the mother thefertile Age Couples (PUS) that have low education in order to improveinformation resources as well as the participation of the husband to knowcontraceptive tools suitable to wear, is expected to bring the insight andknowledge of the fertile age couples (PUSSY) and participation of the husbandabout the selection of contraceptives. Fertile age for couples who have a lowincome in order to keep abreast of the family planning programs that have beendianjur by the Government. Fertile age for couples who have a place to live farfrom health services to keep participated in the family planning program. To thehead of the family or husband to give support or participate to mother to consulton contraception was used.